A Study on Business Implications Due to Automation in Indian Seafood Industry with Specific Reference to the Frozen Sector - V. Vikas, P.; M.K.Badrinarayanan, Dr. (International Journal of Engineering and Technology, 2018)
The global demand for Indian seafood has been rising over the years. Marine product export figures have hit an all time high in terms of both, value and volume. The exports during the year amount up to 11,34,948 megaton values at INR 37870.90 crores, which is approximately USD 6 billion. There are more than 300 frozen seafood processing plants in the country. Some products exported are meant for the retail market and for direct consumer market, however, most of it is meant for reprocessing. This is because most of the technology and machinery used in Indian processing plants are traditional and some processing methods have become outdated. However, exporters are slowly moving towards newer technologies and processing styles in their factories. Value addition is being considered seriously by many seafood exporters. Value added products like IQF, breaded shrimps, marinated seafood, cooked products are now processed in some factories. Even packaging of Indian seafood has undergone many changes like vacuum packing, shrink packaging. Freezing is usually done by ammonia gas, this is now gradually being replaced by a less riskier neon gas in many processing plants. Advanced metal detection systems, highly sensitive water proof weighing scales and palletized automatic operated cold store are some other advancements seen in the recent years. Despite, efforts from various exporters, implementation of all these advancements can be done in large scale only with the help of the government, since such upgradation will incur a lot of investment. With support from various financial institutions, technical help from various government agencies and with the determined perseverance of the exporters, Indian seafood industry can enrich its processing technologies with the latest technology and advanced machinery making it reach great heights globally. This study presents the business implications of automation in the frozen food sector. It also presents the policy implications for implementing automation on a mass scale in the frozen seafood sector.Â Â